2020
DOI: 10.1002/iid3.371
|View full text |Cite
|
Sign up to set email alerts
|

Plasma cytomegalovirus DNA load predicts outcomes in liver transplant recipients

Abstract: Objective Cytomegalovirus (CMV) infection has a significant negative impact on liver transplant (LT) recipients. We aimed to evaluate the efficacy of real‐time DNA quantitative polymerase chain reaction (qPCR) in the early detection of CMV and predicting post‐transplant outcomes. Materials and Methods This was a retrospective study that enrolled a total of 49 adult LT recipients between December 2016 and October 2019. Serial CMV qPCR were tested weekly. We used operating characteristic curve analysis to quanti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…In most cases, CMV infection preceded ABS diagnosis and was virally reactivated. While the relevance of CMV detection and prevention after LT has been largely established, the association between CMV infection and ABS development remains unclear ( 20 22 ). Among the large existing body of literature focused on ABS risk factors, very few series have found similar findings ( 23 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…In most cases, CMV infection preceded ABS diagnosis and was virally reactivated. While the relevance of CMV detection and prevention after LT has been largely established, the association between CMV infection and ABS development remains unclear ( 20 22 ). Among the large existing body of literature focused on ABS risk factors, very few series have found similar findings ( 23 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…This common opportunistic pathogen incurs a more complex infectious condition in immunocompromised recipients following organ transplantation [ 35 , 36 ]. We encourage aggressive CMV treatment once it is detected due to its lethality and many potential risks in transplant recipients [ 8 ]. However, if the clinical presentation of CMV infection becomes latent, we may have some room to make our treatment policy more flexible.…”
Section: Discussionmentioning
confidence: 99%
“…The protocol for the CMV pp65 antigenemia assay was documented in our previous study [ 8 ]. In brief, a blood sample was collected and an antigenemia assay was conducted within 6 h using the MonoFluoTM Kit CMV 52206 Immunofluorescence Assay (IFA; Bio-Rad, Hercules, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gerna et al [ 31 ] found that CMV disease developed in patients with a mean blood CMV viral load of 1740 copies/mL. Assay of CMV DNA by real-time quantitative polymerase chain reaction (PCR)[ 32 - 34 ] showed a cut-off value of 180 copies/mL (164 IU/mL) is associated with an increased incidence of severe CMV disease in adult liver transplant recipients[ 35 ]. The lack of an international reference standard limits the generalization of study cut-off values for worldwide use.…”
Section: Risk Factors Of CMV Infection and Disease After Liver Transp...mentioning
confidence: 99%